The relationship of childhood upbringing and university degree program to environmental identity: experience in nature matters - Prévot, Anne-Caroline; Clayton, Susan; Mathevet, Raphael (Environmental Education Research, 2018)
Education has been proposed as an important way to increase environmental concern. Beyond providing information, education could also encourage a stable sense of oneself as connected to the natural world, or environmental identity (EID), which is a predictor of environmental concern and behavior. This study explored the relative roles of environmental education at university and previous personal characteristics on the level of individual EID. Results from a questionnaire distributed to 919 French students in different academic curricula (ecology, other sciences and political sciences) showed significant difference in levels of EID for students in ecology compared to others, but also that EID was strongly influenced by personal experiences of nature and social context regarding conservation. These results suggest that academic curriculum is more a result than a cause for high environmental identity. We discuss the results in terms of education and access to nature for children and young people.
Keywords: University curriculum; conservation of biodiversity; environmental concern; environmental identity